Rheological Interactions Between Divalent Barium and Sulfate Ions in Hydroxypropyl Guar Polymer Fracturing Fluids - Asmorowati, Dewi; Hidayat, Miftah; Kristanto, Dedi; Hakim Lumban Gaol , Ardhi; Ariadji , Tutuka; Marhaendrajana , Taufan (Scientific Contributions Oil and Gas, 2025)
The use of produced water as a primary component in formulating polymer-based fracturing fluids is becoming a viable option due to the limited availability of fresh water in the field. Nevertheless, the practical use of production water faces several challenges due to its complex composition, which includes monovalent and divalent ions that considerably affect the fluid’s viscosity. Recent studies have shown that calcium ions substantially influence the viscosity of linear fracturing fluids, whereas magnesium ions, do not have a notable effect. However, the effects of other divalent ions commonly found in production water, such as barium and sulfate, remain underreported. In this study, the influence of barium and sulfate ions on linear fracturing fluids will be examined. The viscosity of linear gel fracturing fluids, prepared using hydroxypropyl guar (HPG) polymer with varying concentrations of barium and sulfate ions, will be investigated under different shear rates and temperatures. The results indicate that produced water contains barium and sulfate ions, which affect the rheology of the linear fracturing fluid. A concentration of 150 ppm of BaCl2 can increase the viscosity by 30%, whereas 150 ppm of Na2SO4  increases the HPG viscosity by 7% at ambient temperature (25 °C). At 70 °C, the effect of barium and sulfate ions on the increase in viscosity of the HPG linear fracturing fluid are observed to be less significant.